Discount rates and cash flows: A local projection approach - Lof, Matthijs (Elsevier B.V., 2025)
We develop flexible local projections to quantify the relative contributions of expected discount rates and cash flows to the variation of dividend yields. Local projections enable the incorporation of large information sets, the use of monthly data along with annual data, and the consideration of time variation in the dividend yield decomposition. By expanding the set of state variables and allowing for time-varying parameters, our results show that the variation of expected discount rates remains the primary contributor to market volatility, whereas the contribution of expected cash flows is considerably smaller.